Genome-wide association studies of grain quality traits in maize - Zheng, Yunxiao; Yuan, Fan; Huang, Yaqun; Zhao, Yongfeng; Jia, Xiaoyan; Zhu, Liying; Guo, Jinjie (Scientific reports, 2021)
High quality is the main goal of today’s maize breeding and the investigation of grain quality traits would help to breed high-quality varieties in maize. In this study, genome-wide association studies in a set of 248 diverse inbred lines were performed with 83,057 single nucleotide polymorphisms (SNPs), and five grain quality traits were investigated in diverse environments for two years. The results showed that maize inbred lines showed substantial natural variations of grain quality and these traits showed high broad-sense heritability. A total of 49 SNPs were found to be significantly associated with grain quality traits. Among these SNPs, four co-localized sites were commonly detected by multiple traits. The candidate genes which were searched for can be classified into 11 biological processes, 13 cellular components, and 6 molecular functions. Finally, we found 29 grain quality-related genes. These genes and the SNPs identified in the study would offer essential information for high-quality varieties breeding programs in maize.